Extraction of Permeability Variations from P-Wave Velocity Dispersion Data - Milkereit, B.; Pun, W.; Harris, Brett (EAGE, 2010)
Permeability is a key parameter for the evaluation of subsurface formations in groundwater and hydrocarbon exploration. We utilize broadband full-waveform sonic data to exploit Pride's relationship between P-wave velocity dispersion and permeability for porous, fluid-filled media. Frequency dependent P-wave velocities are extracted from multi-channel sonic data during a two-step process: computation of semblance-based velocity spectra at two or more center frequencies followed by a 2D cross-correlation of the velocity spectra. A comparison with MRI-derived permeability logs confirm that P-wave velocity dispersion logs can be used to map permeability variations.